COMPARASION OF RUSSIAN STRUCTURAL CODE WITH IBC 2009 (US) STRUCTUREAL CODE IN TERMS OF SAFETY AND ECONOMY FOR AFGHANISTAN (Salam International Academic Journal, 2014)
Despite the practical use of International Building Code (IBC) code significantly increased by Afghan engineers during last decade, the Russians codes are still used and are familiar to many structural designers. Need for such documents to assist architects, engineers or code users to enable them transforming from Russian to IBC code were based for this thesis study. In addition, the intent was to indicate the implications of these codes on each other. The comparative analysis is undertaken in sequence based on IBC 2009, structural provisions Chapter 16. The sections of Chapter 16, IBC 2009 are listed sequentially with an analysis of comparison to the Snip 2-01-07.89.    Loads and Stresses Snip 2.01.07-89 1997 design requirements are different in many ways from the structural design provisions given in International Building Code (IBC) 2009, Chapter No.16. However, both codes mainly address the structural design requirements for dead, live, wind, snow, rain, and earthquake loads. As the result of first prototype building analysis comparisons, some differences were found; analysis results in terms of Moments based on IBC 2009 are higher, 30 to 40 percent than analysis results by SNIP 2.01.07-89. The effects mainly caused by the uniformly dead load UDL, safety factors and load combinations that are greater in IBC 2009 than proposed by Snip 2-01-07.89. The result of seismic base shear force calculated by IBC 2009 is smaller about 15 percent with result of seismic base shear force calculated accordance to Afghanistan Seismic Codes (1982-101-1 S / 1983-V-II SQN Afghanistan. The increase in seismic force by Afghanistan code caused by seismic coefficient difference and the building weight due to dead and live load differences. As the result of second prototype building design comparisons, some differences were also found. Design results in terms of flexure reinforcement area and column reinforcements based on IBC 2009 are higher about 50% and -16% than design results by SNIP 2.01.07-89 code for beam and column respectively. For same moment, column axial load and column uniaxial moment, IBC 2009 design reinforcement formulas will provide about 12% more reinforcement area for beam and 69% more reinforcement area for column respectively than calculated by SNIP 2.01.07-89.
Keywords: Comparison; Russian; Structural; IBC; Economy; Afghanistan